Anti‐IL‐7 receptor α monoclonal antibody (GSK2618960) in healthy subjects – a randomized, double‐blind, placebo‐controlled study. Issue 2 (3rd December 2018) - Ellis, Joanne; van Maurik, Andre; Fortunato, Lea; Gisbert, Sophie; Chen, Keguan; Schwartz, Ann; McHugh, Simon; Want, Andrew; Santos Franco, Sara; Oliveira, Joao‐Joaquim; Price, Jeffrey; Coles, Alasdair; et al.
Abstract : Aim: Interleukin (IL)‐7 signalling modulates T cell activity and is implicated in numerous autoimmune diseases. The present study investigated the safety, pharmacokinetics, target engagement, pharmacodynamics and immunogenicity of GSK2618960, an IL‐7 receptor‐α subunit (CD127) monoclonal antibody. Methods: A double‐blind (sponsor‐unblind) study of a single intravenous infusion of either GSK2618960 (0.6 mg kg –1 or 2.0 mg kg –1 ) or placebo was carried out in 18 healthy subjects over 24 weeks. Results: GSK2618960 was well tolerated; there were no serious or significant adverse events. The observed half‐life was 5 (±1) days (2.0 mg kg –1 ), with nonlinear pharmacokinetics. Full receptor occupancy (>95%) was observed until day 8 (0.6 mg kg –1 ) and day 22 (2.0 mg kg –1 ). Maximal inhibition of IL‐7‐mediated signal transducer and activator of transcription 5 (STAT5) phosphorylation was observed in 5/6 subjects until day 22 (2.0 mg kg –1 ). Mean circulating IL‐7 and soluble receptor (CD127) levels were increased above baseline during days 2 and 15 (0.6 mg kg –1 ) and days 2 and 22 (2.0 mg kg –1 ). No meaningful changes were observed in absolute numbers or proportions of immune cell populations or inflammatory cytokine profiles (IL‐6, tumour necrosis factor‐α, interferon‐γ, IL‐2). Persistent antidrug antibodies (ADAs) were detected in 5/6 subjects administered a dose of 0.6 mg kg –1 (neutralizing in 2/6) and in 6/6 subjects administered 2.0 mg kg –1 (neutralizing in 5/6). Conclusion: GSK2618960 was well tolerated and blocked IL‐7 receptor signalling upon full target engagement. Although there was no discernible impact on peripheral T cell subsets in healthy subjects, GSK2618960 may effectively modulate the autoinflammatory activity of pathogenic T cells in diseased tissue. A relatively short half‐life is likely the result of target‐mediated rather than ADA‐mediated clearance.